Social media attacks against female Canadian journalists - Al-Rawi, Ahmed (Frontiers in Communication, 2023)
I investigate in this brief empirical study the social media attacks against female Canadian journalists who have frequently been targeted with online abuse. I used purposive sampling to focus on three journalists: Rachel Gilmore (formerly with Global News), Erica Iffil (freelance with The Hill Times), and Saba Eitizaz (Toronto Star). I employed a mixed method approach to conduct this study by collecting all the available Twitter replies to these three journalists (n=402,821) posted by 84,962 unique users. The digital analysis results show that there are slight differences in the quantity of attacks on these journalists, but the qualitative assessment of images associated with tweets indicate the need to use manual approaches to better understand the nuances and quality of these disinformation and often racist attacks.